Selective detection of DABCO using a supramolecular interconversion as fluorescence reporter - Paul, Indrajit; Samanta, Debabrata; Gaikwad, Sudhakar; Schmittel, Michael (Beilstein Journal of Organic Chemistry, 2019)
The quantitative double self-sorting between the three-component rectangle [Cu4(1)2(2)2]4+ and the four-component sandwich complex [Cu2(1)(2)(4)]2+ is triggered by inclusion and release of DABCO (4). The fully reversible and clean switching between two multicomponent supramolecular architectures can be monitored by fluorescence changes at the zinc porphyrin sites. The structural changes are accompanied by a huge spatial contraction/expansion of the zinc porphyrin–zinc porphyrin distances that change from 31.2/38.8 Å to 6.6 Å and back. The supramolecular interconversion was used for the highly selective detection of DABCO in a mixture of other similar compounds.
Keywords: copper; detection; fluorescence; interconversion; macrocycles; self-assembly; self-sorting; zinc porphyrin